1990
DOI: 10.1002/apmc.1990.051740115
|View full text |Cite
|
Sign up to set email alerts
|

Melt flow and mechanical properties of sulfonated butyl rubber ionomers

Abstract: Study of melt flow properties and mechanical properties of sulfonated butyl rubber ionomers showed that in the case of lithium ionomer addition of zinc stearate lowered obviously the melt viscosity, represented by torque value of a Brabender rheometer, and enhanced tensile strength of the ionomer up to 25% of zinc stearate, while in the case of ethylamine neutralized ionomer addition of zinc stearate lowered the melt viscosity not so obviously as in the case of lithium ionomer and slightly affected the tensile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Figure 1 illustrates that an obvious rubbery plateau appears on the curve of the storage modulus log E′ versus temperature T of sulfonated IIR ionomer neutralized with zinc ion (Zn IIR ionomer). On the other hand, T g1 increases slightly with added zinc stearate, indicating that zinc stearate reduced the association of ionic groups in the ionic domains, decreased the size of domains, and increased the number of physical cross-links, resulting in increasing T g1 and E′ of the rubbery plateau However, excess zinc stearate will separate out as filler [11], causing tensile strength to decrease [7 ]. The rubbery plateau is attributed to the association of ionic bonds between ionomer molecules to form ionic domains or clusters that act as physical cross-links, resulting in appearance of the rubbery plateau.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 illustrates that an obvious rubbery plateau appears on the curve of the storage modulus log E′ versus temperature T of sulfonated IIR ionomer neutralized with zinc ion (Zn IIR ionomer). On the other hand, T g1 increases slightly with added zinc stearate, indicating that zinc stearate reduced the association of ionic groups in the ionic domains, decreased the size of domains, and increased the number of physical cross-links, resulting in increasing T g1 and E′ of the rubbery plateau However, excess zinc stearate will separate out as filler [11], causing tensile strength to decrease [7 ]. The rubbery plateau is attributed to the association of ionic bonds between ionomer molecules to form ionic domains or clusters that act as physical cross-links, resulting in appearance of the rubbery plateau.…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
“…Our former work [7] showed that the sulfonated IIR ionomers neutralized with amines can be processed without addition of ionic plasticizer. This may be related to their lower T g1 , T E″1 and lower modulus E′, as well as a narrower temperature range of rubbery plateau.…”
Section: Dynamic Mechanical Properties Of the Butyl Rubber Ionomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al reported the melt flow properties, solution behavior, dynamic mechanical properties and mechanical properties of sulfonated EPDM ionomers (4) and butyl rubber ionomers (5), both of which were obtained by sulfonation with acetyl sulfate in petroleum ether and neutralization with metallic acetates or alkylamines. It was pointed out that it is not necessary to use zinc stearate during processing of alkylamine neutralized ionomers of sulfonated butyl rubber (5). However, Fitzgerald and Weiss (6) pointed out that the rubber with higher unsaturation degree cannot be sulfonated in solution in concentration over 3% so as to avoid gelation.…”
Section: Introductionmentioning
confidence: 99%
“…Canter4 obtained butyl rubber ionomers through the sulfonation of butyl rubber with a SO 3 /triethyl phosphate complex, followed by neutralization with NaOH, and studied their mechanical properties. Xie and coworkers reported the melt‐flow properties, solution behavior, dynamic mechanical properties, and mechanical properties of sulfonated EPDM ionomers5 and butyl rubber ionomers,6, 7 both of which were obtained by sulfonation with acetyl sulfate in petroleum ether and neutralization with metallic salts or alkylamine. They pointed out that it was not necessary to use zinc stearate during the processing of alkylamine‐neutralized ionomers of sulfonated butyl rubber.…”
Section: Introductionmentioning
confidence: 99%